Social Media, Spirituality, and Consumerism: A Case Study of Marketing Spiritual Learning at SOUL - Anak Agung Gede Putra; Ida Bagus Gde Yudha Triguna; I Gusti Agung Paramita (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2026)
This study examines the transformation of contemporary spirituality within a digital ecosystem shaped by consumer logic, using SOUL (Spirit of Universal Life) as the case study. Through the original analytical framework The Maker–The Market–The Meaning (3M), the research addresses how SOUL leverages social media to package and market spiritual learning; how commodification of meaning operates within SOUL's marketing ecosystem; and what implications these practices hold for audiences' spiritual subjectivity. A critical-interpretive qualitative approach combining digital ethnography (netnography) and Critical Discourse Analysis (CDA) was employed, with a critical paradigm as the epistemological meta-framework to manage researcher bias given the author's insider position as SOUL's CMO. Three key findings emerge: (1) The Maker builds digital spiritual authority through figural performativity, translation of teachings into social media formats, and self-technology tools (SOUL Meter and SOUL Care); (2) The Market reveals community evolution into spiritual prosumers unified by an "energy barter" logic that provides cosmological legitimacy for paid exchanges; (3) The Meaning discloses new subjectivities in which participants understand themselves as souls growing and returning home, experiencing tangible transformation across relational, economic, and religious dimensions. The study proposes the concept of managed spirituality — spirituality packaged and delivered through curricula and self-technologies — while critically exposing its inherent ambivalence: emancipatory yet potentially constraining. These findings demonstrate that commodification of meaning need not be contradictory to authentic spirituality within Indonesia's digital spiritual economy.